The Role of Self-Construal, Values, and Religiosity on Judgements of the Reasonability of Lying - Sercan Balım; Muhammed Sukru Aydın (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
Although lying, which is a social part of human life, is seen as a negative phenomenon in society, it is considered quite reasonable by people in some cases. In this respect, it is important to examine in which circumstances lying is acceptable. This study aims to examine the relationships between self-construal, values, religiosity, and the acceptability of different types of lies. A total of 605 participants completed the self-report measures of the Reasonability of Lying Scale, Portrait Values Questionnaire, and Autonomous-Related Self Scale. In addition, considering possible response biases, social desirability scores were also controlled. The results of the hierarchical regression analysis showed that religiosity, conservation, and self-enhancement values were the predictors of acceptability of self-protection lies. In terms of the acceptability of face management lies, conservation and self-enhancement values, and autonomous-relational self were the significant predictors. It was founded that the only variable that was a significant predictor of acceptability of prosocial lie was self-transcendence values. Acceptability of evasion lies were significantly predicted by religiosity and autonomous-relational self. Another finding was that religiosity, conservation and self-enhancement values and autonomous-relational self-construal were the significant predictors of acceptability of necessity lies. The results showed that religiosity, conservation and self-enhancement values, and autonomous-relational self-construal variables were significant predictors of acceptability of instrumental lies. Finally, in terms of the total acceptability of different types of lies; religiosity, conservation and self-enhancement values and autonomous-relational self-construal variables were the significant predictors. The results obtained from this study indicate that evaluations of lying are affected by different social factors, and these factors are discussed in the light of recent findings.